1995
DOI: 10.1007/bf00202660
|View full text |Cite
|
Sign up to set email alerts
|

Polar distribution of annexin-like proteins during phytochrome-mediated initiation and growth of rhizoids in the ferns Dryopteris and Anemia

Abstract: Although the calcium requirement of phytochrome-mediated fern spore germination and early rhizoid growth is well established, the calcium-binding proteins that serve as transducers for these responses are not known. Here we report the presence of annexin-like proteins in germinating spores of Dryopteris filix-mas (L.) Schott and Anemia phyllitidis (L.) Sw. and evidence that they may be important participants in early photomorphogenic changes in gametophytes. Immunolocalization and immunoblot assays of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…These 2 proteins might be encoded by divergent mRNAs, not detected by the E511 cDNA probe. The 2 other proteins are not recognized by the maize antiserum, but the use of antibodies from mammals can provide an alternative assay to detect other annexins (immunoblottings were carried out using polyclonal antibodies raised against anchorin CII from chicken to identify annexins in the fern rhizoids) [18].…”
Section: Discussionmentioning
confidence: 99%
“…These 2 proteins might be encoded by divergent mRNAs, not detected by the E511 cDNA probe. The 2 other proteins are not recognized by the maize antiserum, but the use of antibodies from mammals can provide an alternative assay to detect other annexins (immunoblottings were carried out using polyclonal antibodies raised against anchorin CII from chicken to identify annexins in the fern rhizoids) [18].…”
Section: Discussionmentioning
confidence: 99%
“…These different isoforms may represent a single gene product that has undergone posttranslational modification, such as phosphorylation, or different gene products, such as seen in rat liver, where three different annexin gene products co-migrate at 35 kD on SDS-PAGE (Kaetzel et al, 1989). High molecular mass (67-70 kD) annexins have been observed in Tradescantia, maize, peas, and ferns (Blackbourn et al, 1991;Clark et al, 1995). cDNA sequence data for these higher molecular mass annexin-like proteins will resolve whether these proteins are homologous with annexin VI, which has eight repeats, or represent a stable dimer caused by transglutamination, as observed in the case of annexin I (Ando et al, 1989(Ando et al, , 1991.…”
Section: Purlflcatlon a N D Biochemical Propertiesmentioning
confidence: 99%
“…The staining pattern in pea and corn seedlings reveals that annexins are highly concentrated in secretory cell types, such as the outer cells of the root cap, epidermal cells, and developing xylem and phloem cells (Clark et al, 1992(Clark et al, , 1994. Immunolocalization results also indicate that there are high levels of annexins in the tip region of polarly growing cells such as pollen tubes and fern rhizoids, cell types that are actively involved in the Golgi-mediated secretion of new wall materials and plasma membrane (Blackbourn et al, 1992;Clark et al, 1995). In the case of pollen tubes it has been shown that there are higher levels of Ca2+ at the tip (Miller et al, 19921, and it has been suggested that annexins may be one target for this Ca2+ signal.…”
Section: Dlstrlbutlon a N D Localizationmentioning
confidence: 99%
See 2 more Smart Citations